Modification of Cellulose and Lignocellulose Materials with Nanoсlusters of Copper Ferrocyanides - V. V. Galysh; M. T. Kartel (Хімія, фізика та технологія поверхні)
A possibility of obtaining of new combined sorbents based on bleach cotton fiber and lignocellulose complex from apricot stones modified with nanoclusters of copper ferrocyanides [FC]Cu has been studied. A relation has been found between the modifier concentration in the initial solution, its content in the obtained combined sorbents, size agglomerates, and sorption capacity for 137Cs. It has been found that in terms of practical significance, the content of the modifier in the bulk of organic carriers about 4–4.5% provides high sorption capability of synthesized materials for radiocaesium. The most efficiency of use of [FC]Cu mass in sorption of 137Cs corresponds to combined sorbents containing 2–2.5% [FC]-phase.